2018
DOI: 10.1590/1981-52712015v42n3rb20180047ing
|View full text |Cite
|
Sign up to set email alerts
|

Medical Residents Perceptions of Communication Skills a Workshop on Breaking Bad News

Abstract: Introduction Breaking bad news althoughfrequent among healthcare professionals and their patients is still considered a very difficult task. These communication skill main determinants in the physician-patient relationship. Objective In view of the need to promote academic spaces that provide opportunities to learn breaking bad news , thisstudy aims to evaluate the medical residentsin relation to their interest in learning communication skills, as well as their skills in breaking bad news, before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…When asked to rate their communication skill level, the majority of them perceived it as good, very good, or excellent. This is compatible with other global studies conducted in settings where patient-centred communication was given high priority and recognised as a learning interest [10,11].…”
Section: Discussionsupporting
confidence: 89%
“…When asked to rate their communication skill level, the majority of them perceived it as good, very good, or excellent. This is compatible with other global studies conducted in settings where patient-centred communication was given high priority and recognised as a learning interest [10,11].…”
Section: Discussionsupporting
confidence: 89%
“…There are few studies about advance care planning skills designed for medical residents that have been evaluated for their effectiveness [ 27 , 28 , 29 ]. Some authors demonstrated that communication skills training programs may improve residents’ skills in breaking bad news with a positive change in their emotional reactions after training and minimizing insecurity to talk about challenging issues such as prognosis [ 24 , 27 , 28 , 29 , 30 ]. In the qualitative analysis of the present study, most of the residents suggested the communication skills training and the ability to talk about prognosis early as strategies to facilitate advance care planning and goals of care discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, os profissionais comunicadores dessas notícias costumam salientar suas habilidades de CND desenvolvidas após seu período acadêmico 13 . Muitos profissionais médicos acabam necessitando de um preparo prévio para atenuar essas dificuldades, na comunicação, e diminuir as repercussões negativas que possam gerar.…”
Section: Discussionunclassified